HERV-K10 as a mediator of immune modulation in hepatitis infections - Özer, Salih; Strobelt, Romano; Kosinska, Anna D.; Frishman, Goar; Wettengel, Jochen M.; Pleninger, Lisa; Körber, Nina; Liang, Wen; Ates Öz, Edanur; Zuniga, Marisol; Bauer, Tanja; Ebert, Gregor; et al. (Frontiers in Immunology, 2025)
The human genome contains ~8% of endogenous retroviruses (HERVs), whose reactivation has been implicated in diseases such as cancer and autoimmune disorders. Among these, HERV-K10 has attracted attention for its potential role in immune modulation and viral infections. This study investigates HERV-K10 expression in hepatitis virus infections, focusing on its impact on host gene expression and immune responses. We analyzed HERV-K10 in PBMCs from patients chronically infected with hepatitis C virus (HCV) and in HBV-infected liver cell models. Our results show a significant upregulation of HERV-K10 in HBV-infected HepG2-NTCP cells, HCV-infected PBMCs, and a trend in HBV-infected primary hepatocytes. HERV-K10 activation was specific to hepatitis infection, as no effect was seen with HBV entry inhibitors, adenovirus 5 infection or infection with other RNA viruses. RNA sequencing of HBV-infected HepG2-NTCP cells revealed distinct clustering based on HERV expression profiles, including HERV-K10 encoding the MAG1 domain, an immune response target. To investigate the potential immunomodulatory role of HERV-K10 MAG1, we vaccinated mice with the MAG1 peptide, which resulted in activation of CD4+ and CD8+ T-cell responses and higher levels of MAG1-specific antibodies. Furthermore, chronic hepatitis B patients exhibited an immune response to MAG1 characterized by elevated levels of Interleukin-6 (IL-6) and interleukin-1β (IL-1β) cytokines. Taken together, our data suggest that HERV-K10 plays an important role in immune modulation during viral hepatitis infection and may contribute to the pathogenesis of autoimmune diseases.